(untitled) (University Arena, 2025)
Background. As we know, football is worldwide considered, by specialists and not only by them, the most beloved sports discipline practiced by a huge number of young people all over the world. In this regard, the paper aims to demonstrate the usefulness and necessity of conducting studies and researches meant to improve the successful completion of the attacks for goal scoring in elite football. Objectives. As an act of scientific research, this paper has certain objectives set as benchmarks: determining the real image of the technical-tactical profile of the team (in terms of long shots) based on the official games records regarding the attack actions mentioned above; centralization of the attacking phases and their achievement (per player, per completion, per player) and the way to improve and implicitly adapt the contents of the training session; correlation of the tactical tasks established by the coach with the actual possibilities of F. C. Voluntari team players and counting of these issues; making the players aware of how they fulfill the tactical responsibilities of an official game and giving immediate feedback by systematically presenting the tactical actions performed by the players in each game. Methods. The following methods were used to conduct this research: study of the specialized literature documents; discussion method; method of observation and recording, statistical-mathematical and graphical representation method. The study was carried out in “F. C. Voluntari” Football Club. The observation, discussions, obtained data and records took place throughout the Championships of Division B, 2009-2010 edition. The measurements referred to: recording by observation and assistance in official and friendly games, both in and out, during the team training sessions as well; data comparison; determination of the share of “shots for goal “ of the players included in this team. The records began in the 2nd stage, on August 17, 2009 and were concluded on May 24, 2010, in the 28th stage of that competitive season. There were made 15 sheets monitoring the number of shots: by distance, by execution pattern (from stationary moments and from action), all over the game, divided into 2 halves and 5 record protocols during the training sessions. Results. The analysis of the results proves the evolution of the shot on goal technique which is essentially determined by the discovery and highlighting of biomechanics data and which influenced decisively the performance level all over the years. The changes occurred in the shot technique were supported in parallel by special modifications of the training, especially with regard to the development of motor skills (strength, speed) aiming to increase the efficiency. The study demonstrated that the team of F. C. Voluntari Bucharest, implementing the programs for long shot improvement in their training sessions, achieved the expected results and reached the objectives set for the current season. A higher efficiency of the shots made from action was found out, namely: 65.1% of the shots were made from action and only 34.9% from stationary phases. Conclusion. In order to achieve performance, the practice of the shots on goal is an essential factor of the football game. This can be done in special training sessions, using the records of the games.